Hepatic infarction and acute pancreatitis: a case report and review of the literature - Kulkarni, Archana; Arif, Hamza; Veer, Manik; Ziggas, Kateyln; Kaura, Amit; Sareen, Meera (Clinical and Experimental Hepatology, 2018)
Hepatic infarction is rare due to the unique dual hepatic blood supply from the hepatic artery and the portal vein. Herein, we report a case of hepatic infarction that occurred as a complication of acute pancreatitis. The patient was a 58-year-old male with past medical history of chronic alcoholism, who presented with epigastric abdominal pain, nausea, and vomiting. Hepatic infarction was diagnosed with computed tomography of the abdomen and pelvis without contrast, which revealed suspicion of splenic vein thrombosis and peripancreatic fat stranding along with a wedge-shaped, peripheral hypo density in the right hepatic lobe with typical morphology for hepatic infarction.